Romantic rhyme and the airs that stray - Clarkson, O; Hodgson, A (Edinburgh University Press, 2017)
Romantic poetry is striking for the richness and variety of its rhymes. If it is concerned to resist the constraints rhyme might impose, it also harnesses those constraints as a source of creativity, stimulating both comedy and pathos. This essay shows that Romantic poets find in rhyme a resource which amplifies many of their defining concerns: a fascination with incongruous states of vision, a desire to reconcile oneness and variety, and an aspiration to capture without arresting the evanescence of experience. Rhyme in the hands of Romantic poets, we suggest, speaks of disharmonies as much as of harmonies, and we conclude by pointing to the ways that later poets are both challenged and inspired by Romantic rhyme.